Determinants of firm profitability in the Croatian manufacturing industry: evidence from dynamic panel analysis. Issue 1 (1st January 2019) - Pervan, Maja; Pervan, Ivica; Ćurak, Marijana
Abstract: Given that the goal of this study was to examine the influence of different factors on a firm's profitability, we designed a model with three categories of profitability determinants: firm-specific, industry-specific and macroeconomic. The analysis was performed on 9359 firms operating in the Croatian manufacturing industry during the 2006–2015 period. Since the designed model was formulated in a way that encompasses the dynamic aspect of profitability, the General Method of Moments (G.M.M.) dynamic panel estimator was applied. Formulation of such a model adds to the existing literature if one takes into account that a dynamic analysis of the drivers of profitability has not been done using data from the Croatian manufacturing sector. The results of the conducted analysis revealed that a firm's age, labour cost and industry concentration, as well as G.D.P. growth and inflation, have significant influence on a firm's profitability.